2007
DOI: 10.1021/ol702684d
|View full text |Cite
|
Sign up to set email alerts
|

A Metathesis-Based Approach to the Synthesis of 2-Pyridones and Pyridines

Abstract: The ring-closing metathesis reaction has been successfully employed to form a range of dihydropyridone intermediates, which are in the correct oxidation state to undergo a base-induced elimination to reveal the aromatic 2-pyridone. This mild and novel approach to six-membered heteroaromatic compounds then provides access to a wide variety of substituted pyridines in excellent overall yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 32 publications
(15 reference statements)
1
32
0
1
Order By: Relevance
“…Milrinone and their analogues which have 2-pyridone moiety are used as cardiotonic agents for the treatment of heart failure [6]. Owing to their luminescent and immense biological properties, substituted 2-pyridone derivatives are catching much interest in the development of simple and convenient methodologies for the synthesis from easily available starting materials [7]. Many synthesis methods of 2-pyrone have been reported to date [8], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Milrinone and their analogues which have 2-pyridone moiety are used as cardiotonic agents for the treatment of heart failure [6]. Owing to their luminescent and immense biological properties, substituted 2-pyridone derivatives are catching much interest in the development of simple and convenient methodologies for the synthesis from easily available starting materials [7]. Many synthesis methods of 2-pyrone have been reported to date [8], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This idea was delineated by the Donohoe group who showed that N-alkoxy acrylamides 56 undergo smooth ring closure using HG2 to provide cyclic acrylamides 57 (Scheme 18a) [63][64][65]. These systems underwent base-induced E1cB elimination of BnOH or MeOH to provide NH pyridones (e.g.…”
Section: Synthesis Of Pyridones Pyridines Pyridazinones and Pyridazmentioning
confidence: 99%
“…Nachdem sich Sutter erfolglos daran versucht hatte, offenkettige 2,5-Dioxoadipinsäure (2,5-Dioxohexandisäure, 6) darzustellen [11], berichteten Haworth et al im Jahre 1938 ohne Angabe einer Ausbeute vom Erfolg eben jener Synthese [12]. Sie charakterisierten sowohl das Pyron 5 als auch eine offenkettige C 6 -Disäure ( " α,α -Diketoadipinsäure") mittels UV/Vis-Spektroskopie und postulierten für erstgenanntes in wässriger Lösung Es ist alles andere als trivial, die Reaktionskaskade aus vierfacher Verseifung, zweifacher Decarboxylierung und gegebenenfalls Zyklisierung von 3, die zu 2,5-Dihydroxymuconsäure (4), 2,5-Dioxoadipinsäure (6) oder 3-Hydroxy-2-oxo-2H-pyran-6-carbonsäure (5) Nur in wenigen Fällen haben wir bei der sauren Hydrolyse von 3 ebenfalls in Diethylether unlösliche 2,5-Dihydroxymuconsäure (4) [27]. Für die Zielverbindung Methyl-5-(benzyloxy)-6-oxo-1,6-dihydropyridin-2-carboxylat (11) wurde eine konvergente Route vorgestellt, deren Schlüssel-schritt eine Ringschlussmetathese (RCM) mit dem Hoveyda-Grubbs-Katalysator der 2.…”
Section: Synthesewegeüber Ester Von 25-dioxoadipinsäure Und 25-dihyunclassified